Emerging Perovskite Solar Cell Technology: Remedial Actions for the Foremost Challenges. Issue 42 (3rd October 2021) - Sahare, Sanjay; Pham, Hong Duc; Angmo, Dechan; Ghoderao, Prachi; MacLeod, Jennifer; Khan, Sadaf Bashir; Lee, Shern‐Long; Singh, Samareandra P.; Sonar, Prashant
Abstract: Perovskite solar cells (PSCs) exhibit the steepest growth in power conversion efficiency among the existing photovoltaic technologies. However, a wide range of factors restrict the commercial viability of PSCs as a renewable energy source. This article reviews the latest progress in PSC devices including innovative light‐harvesting perovskite materials and advanced interfacial layers, and the foremost challenges. The most promising remedial solutions to challenges are also discussed. For the realization of a high performing and eco‐friendly stabilized perovskite photovoltaic device, a combinational method involving multiple restorative solutions is required. A specific emphasis is given to unveiling interesting perovskite properties, and device fabrication approaches to the solutions. These remedies and strategies may help researchers to select appropriate methods and design their experiments to obtain a high photo‐conversion efficiency in photovoltaic devices with enhanced stability as compared to conventional photovoltaic devices. Abstract : This article reviews the foremost challenges in the perovskite solar cells (PSCs) and provides advanced remedial solutions including innovative light‐harvesting perovskites, advanced interfacial layers, device engineering, and encapsulations of the devices. These remedies and strategies may help researchers to select the appropriate methods and design their experiments to obtain high photo‐conversion efficiency in the PSCs for commercial solar cell development.